Pengembangan Game Edukasi Construct 2 pada Pembelajaran Biologi Materi Hormon pada Reproduksi Manusia - Nasikhatul Khusna; Fahrur Rozy (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Educational game learning media provides a systematically arranged digital platform for self-study. These games can effectively complement traditional teaching materials, supporting students' independent learning both at home and outside regular school hours. This researchspecifically aimed to develop a feasible educational game using Construct 2 for Biology Subject on Human Reproduction Hormones, targeting Class XI Science students at MA Al Fatahiyyah.The study employed a Research and Development (R&D) approach, guided by the ADDIE development model (Analyze, Design, Develop, Implement, Evaluate). The content of the developed game media was carefully aligned with the Class XI MA Al Fatahiyyah syllabus,focusing on the